2021
DOI: 10.1038/s41598-021-87324-6
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair and open repair surgery of thoraco-abdominal aortic aneurysms cause drastically different types of spinal cord injury

Abstract: Both endovascular repair (EVR) and open repair (OR) surgery of thoraco-abdominal aortic aneurysms cause spinal cord (SC) injury that can lead to paraparesis or paraplegia. It has been assumed that mechanisms responsible for SC damage after EVR are similar to those after OR. This pilot study compared the pathophysiology of SC injury after EVR versus OR using a newly developed EVR dog model. An increasing number of stents similar to those used in patients were inserted in the aorta of three dogs to ensure thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Although SCI following endovascular repair is mostly attributed to hemodynamic compromise from insufficient collaterals to the spine and the ensuing edema, recent evidence also points to embolic mechanism as an equally important phenomena 25 . Therefore, differences in mechanism of SCI and in the risk associated with CSFD after FB-EVAR may justify a change in strategy 26–29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SCI following endovascular repair is mostly attributed to hemodynamic compromise from insufficient collaterals to the spine and the ensuing edema, recent evidence also points to embolic mechanism as an equally important phenomena 25 . Therefore, differences in mechanism of SCI and in the risk associated with CSFD after FB-EVAR may justify a change in strategy 26–29 …”
Section: Discussionmentioning
confidence: 99%
“…25 Therefore, differences in mechanism of SCI and in the risk associated with CSFD after FB-EVAR may justify a change in strategy. [26][27][28][29] The evidence regarding use of prophylactic CSFD during endovascular thoracic and thoracoabdominal aneurysm repair derives from retrospective noncomparative studies. In contrast to the open surgical literature, there are no randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, two types of TAAA repair surgery are used: OR surgery, that requires ACC to replace the weak and bulging section of the aorta by a graft, and endovascular repair, that consists of stenting the aorta through the femoral artery. We recently developed two dog models that allowed us to compare the pathophysiology of paraplegia after these two surgical procedures, and found that, in contrast to open repair that causes massive gray matter damage and neuronal death as a result of transient, severe ischemia followed by rapid reperfusion, endovascular repair primarily induces white matter damage associated with limited neuronal death as a consequence of extended hypoperfusion (Awad et al, 2021b). As there is presently no preventive pharmaceutical treatment against complications for either procedure, and given the frequency of aortic aneurisms (6-10 per every 100,000 people, with 9,923 deaths recorded in the United States in 2018), it is critical to understand the molecular dysfunctions that lead to similar percentages of paraplegia after these two surgical procedures (Rocha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most devastating complications of either open surgical or endovascular repair of aortic aneurysms is spinal cord ischemia and/or paralysis. Although both treatment paradigms have a risk of postoperative paralysis, there are different mechanisms which govern the pathophysiology of open aortic surgery and thoracic endovascular aortic repair (TEVAR) mediated paralysis [ 146 ]. A recently published article demonstrated in a large animal model that these two mechanisms are different.…”
Section: Part 2 – Selected Gaps In Knowledge and Future Direction Of ...mentioning
confidence: 99%